Time-response characteristic and potential biomarker identification of heavy metal induced toxicity in zebrafish. Issue 72 (January 2018) - Yin, Jian; Wang, Ai-Ping; Li, Wan-Fang; Shi, Rui; Jin, Hong-Tao; Wei, Jin-Feng
Abstract: The present work aims to explore the time-response (from 24 h to 96 h) characteristic and identify early potential sensitive biomarkers of copper (Cu) (as copper chloride dihydrate), cadmium (Cd) (as cadmium acetate), lead (Pb) (as lead nitrate) and chromium (Cr) (as potassium dichromate) exposure in adult zebrafish, focusing on reactive oxygen species (ROS), SOD activity, lipid peroxidation and gene expression related to oxidative stress and inflammatory response. Furthermore, the survival rate decreased apparently by a concentration-dependent manner after Cu, Cr, Cd and Pb exposure, and we selected non-lethal concentrations 0.05 mg/L for Cu, 15 mg/L for Cr, 3 mg/L for Cd and 93.75μg/L for Pb to test the effect on the following biological indicators. Under non-lethal concentration, the four heavy metals have no apparent histological change in adult zebrafish gills. Similar trends in ROS production, MDA level and SOD activity were up-regulated by the four heavy metals, while MDA level responded more sensitive to Pb by time-dependent manner than the other three heavy metals. In addition, mRNA levels related to antioxidant system (SOD1, SOD2 and Nrf2) were up-regulated by non-lethal concentration Cu, Cr, Cd and Pb exposure. MDA level and SOD1 gene have a more delayed response to heavy metals. Genes related to immunotoxicity were increased significantly after heavy metals exposure at non-lethal concentrations. TNF-α and IL-1β gene have similar sensibility to the four heavy metals, while IL-8 gene was more responsive to Cr, Cd and Pb exposure at 48 h groups and IFN-γ gene showed more sensitivity to Cu at 48 h groups than the other heavy metals. In conclusion, the present works have suggested that the IFN-γ gene may applied as early sensitive biomarker to identify Cu-induced toxicity, while MDA content and IL-8 gene may use as early sensitive biomarkers for evaluating the risk of Pb exposure. Moreover, IL-8 and IFN-γ gene were more responsive to heavy metals, which may become early sensitive and potential biomarkers for evaluating inflammatory response induced by heavy metals. This work reinforces the concept of the usefulness of gene expression assays in the evaluation of chemicals effects and helps to establish a background data as well as contributes to evaluate early environmental risk for chemicals, even predicting toxicity. Graphical abstract: Highlights: The IFN-γ gene may applied as a sensitive biomarker to identify Cu-induced toxicity. The IL-8 gene is more sensitive to Cr and Cd exposure than Cu and Pb. The MDA level and IL-8 gene are sensitive to Pb exposure. IL-8 and IFN-γ gene are sensitive biomarkers for evaluating heavy metal exposure. Difference sensitivity between SOD1 and SOD2 may be characteristic of heavy metals.